Blue lights. [Series 1] [videorecording (DVD)] - Harris, Fran; Lawn, Declan; Patterson, Adam (Writer); McCann, Martin, 1983-; Brooks, Sian; Carver, Matt; Braniff, Nathan (BBC, 2024)
In Belfast, three PSNI recruits fight gangs, undercover agents and even their own force.